Pengaruh Audit Internal, Struktur Modal, Dan Good Corporate Governance Terhadap Kinerja Keuangan - Amara Meidiana; Erinos NR (Jurnal Eksplorasi Akuntansi, 2020)
Economic growth according to business field said that financial sector in 2016 to 2018 were decreased year by year. It indicates that there was a financial performance’s decline in financial sector’s companies. In order to increase financial performance, we need to find out factors that could accelerate financial performance’s potential. Internal audit, capital structure, and good corporate governance are independent variables that will be tested in this research for their impacts on financial performance. This research uses ROA, ROE, & NPM combination as internal audit’s proxies and DAR, DER, & LDER as capital structure’s proxies which are still minor in prior researchs. The purpose of this research is to test how far internal audit, capital structure, and good corporate governance could affect financial performance partially. This research was tested on financial sector’s companies that listed on Indonesia Stock Exchange in 2016 to 2018 with 129 samples using purposive sampling method with judgment. The results of this research proved that internal audit had insignificant positive impact on financial performance, capital structure had significant negative impact on financial performance, while good corporate governance had significant positive impact on financial performance with significant level 0,005 which is had not reach the maximum standard 0,05 yet.